Antimicrobial Peptides and Complement in Neonatal Hypoxia-Ischemia Induced Brain Damage - Rocha-Ferreira, Eridan; Hristova, Mariya (Frontiers in Immunology, 2015)
Hypoxic-ischemic encephalopathy (HIE) is a clinical condition in the neonate, resulting from oxygen deprivation around the time of birth. HIE affects 1-5 per 1000 live births worldwide and is associated with the development of neurological deficits, including cerebral palsy, epilepsy and cognitive disabilities. Even though the brain is considered an immune-privileged site, it has innate and adaptive immune response and can produce complement (C) components and antimicrobial peptides (AMPs). Dysregulation of cerebral expression of AMPs and C can exacerbate or ameliorate the inflammatory response within the brain. Brain ischemia triggers a prolonged inflammatory response affecting the progression of injury and secondary energy failure and involves both innate and adaptive immune systems, including immune-competent and non-competent cells. Following injury to the central nervous system (CNS), including neonatal hypoxia-ischemia (HI), resident microglia and astroglia are the main cells providing immune defence to the brain in a stimulus-dependent manner. They can express and secrete pro-inflammatory cytokines and therefore trigger prolonged inflammation resulting in neurodegeneration. Microglial cells express and release a wide range of inflammation-associated molecules including several components of the complement system. Complement activation following neonatal HI-injury has been reported to contribute to neurodegeneration. Astrocytes can significantly affect the immune response of the CNS under pathological conditions through production and release of pro-inflammatory cytokines and immunomodulatory AMPs. Astrocytes express β-defensins which can chemoattract and promote maturation of dendritic cells, and can also limit inflammation by controlling the viability of these same dendritic cells. This review will focus on the balance of complement components and AMPs within the CNS following neonatal HI-injury and the effect of that balance on the subsequent brain damage.